The Impact of Quercetin and Its Methylated Derivatives 3-o-Methylquercetin and Rhamnazin in Lipopolysaccharide-Induced Inflammation in Porcine Intestinal Cells - Zita Karancsi; Dóra Kovács; Nikolett Palkovicsné Pézsa; Péter Gálfi; Ákos Jerzsele; Orsolya Farkas (MDPI AG, 2022)
Oxidative stress in the small intestine can lead to inflammation and barrier malfunction. The present study describes the effect of quercetin (Q), 3-o-methylquercetin (QM), and rhamnazin (R) on cell viability, paracellular permeability, production of intracellular reactive oxygen species (ROS), extracellular hydrogen peroxide (H2O2), and interleukin-6 (IL-6) after challenging jejunal cells (IPEC-J2) with different types (Salmonella enterica ser. Typhimurium, Escherichia coli O111:B4, and E. coli O127:B8) of lipopolysaccharides (LPS) applied in 10 µg/mL concentration. The intracellular ROS level increased after all LPS treatments, which could be decreased by all tested flavonoid compounds in 50 µM concentration. Extracellular H2O2 production significantly increased after Q and R treatment (50 µM). S. Typhimurium LPS could significantly increase IL-6 production of enterocytes, which could be alleviated by Q, QM, and R (50 µM) as well. Using fluorescein isothiocyanate dextran (FD4) tracer dye, we could demonstrate that S. Typhimurium LPS significantly increased the permeability of the cell layer. The simultaneous treatments of S. Typhimurium LPS and the flavonoid compounds showed no alteration in FD4 penetration compared to untreated cells. These results highlight that Q, QM, and R are promising substances that can be used to protect intestinal epithelial cells from the deteriorating effects of oxidative stress.